ANALISA VARIABEL FUNDAMENTAL TERHADAP HARGA SAHAM PERUSAHAAN GO PUBLIC DI BEI - Hartono, Hartono (Fakultas Ekonomi Universitas PGRI Adi Buana, 2015)
This aim of the research is to find out the proof and the clarity about phenomenon influence of fundamental factor and systematic risk on stock price of manufacturing business which is listed in Indonesia Stock Exchange (ISX), either is partially and simultaneously. The object of this research is all of the manufacturing business enlisted in Indonesia Stock Exchange (ISX) since 2010 – 2013, and publish the financial statement, getting profit and have obligation during observation year. Technique test of data is by using simple linear regression to test by parsial and multiple linear regression to test by simultan, by level significant alpha 5%. The result of this research prove that the fundamental factor and systematic risk influence on stock price, while ROA, DER and Beta have influenced on stock price simultaneously, and BVS does not influenced on the stock price significantly.